Quantification of groundwater storage variation in Himalayan & Peninsular River basins correlating with land deformation effects observed at different Indian cities - SARKAR, Tandrila; KARUNAKALAGE, Anuradha; KANNAUJIYA, Suresh; CHAGANTI, Charan (Contributions to Geophysics and Geodesy, 2022)
Groundwater is a significant resource that supports almost one-fifth population globally, but has been is diminishing at an alarming rate in recent years. To delve into this objective more thoroughly, we calculated interannual (2002–2020) GWS (per grid) distribution using GRACE & GRACE-FO (CSR-M, JPL-M and SH) Level 3 RL06 datasets in seven Indian river basins and found comparatively higher negative trends (−20.10 ± 1.81 to −8.60 ± 1.52 mm/yr) in Basin 1–4 than in Basin 5–7 (−7.11 ± 0.64 to −0.76 ± 0.47 mm/yr). After comparing the Groundwater Storage (GWS) results with the CHIRPS (Climate Hazards Group Infrared Precipitation with Stations) derived SPI (Standardized Precipitation Index) drought index, we found that GWS exhausts analogously in the same period (2005–2020) when SPI values show improvement (∼1.89–2), indicating towards wet condition. Subsequently, the GWSA time series is decomposed using the STL (Seasonal Trend Decomposition) (LOESS Regression) approach to monitor long-term groundwater fluctuation. The long term GWS rate (mm/yr) derived from three GRACE & GRACE-FO solutions vary from −20.3 ± 5.52 to −13.19 ± 3.28 and the GWS mass rate (km3/yr) lie in range of −15.17 ± 4.18 to −1.67 ± 0.49 for basins 1–3. Simultaneously, in basin 4–7 the GWS rate observed is −8.56 ± 8.03 to −0.58 ± 7.04 mm/yr, and the GWS mass rate differs by −1.71 ± 0.64$ to −0.26 ± 3.19 km3/yr. The deseasonalized GWS estimation (2002–2020) states that Himalayan River basins 1,2,3 exhibit high GWS mass loss (−260 to −35.12 km3), with Basin 2 being the highest (−260 km3). Whereas the Peninsular River basin 4,6,7 gives moderate mass loss value from −26.72 to −23.58 km3. And in River basin 5, the GWS mass loss observed is the lowest, with a value of −8 km3.